2021
DOI: 10.1080/20008198.2021.1947564
|View full text |Cite
|
Sign up to set email alerts
|

The association between COVID-19 related stressors and mental health in refugees living in Australia

Abstract: Background Refugees may be particularly vulnerable to the adverse effects of the COVID-19 pandemic on mental health due to their traumatic pasts and the challenges of the postmigration environment. Objective To evaluate the prevalence of COVID-19 related stressors and their relationship to key mental health and functioning outcomes in a resettled refugee sample. Method N = 656 refugees and asylum seekers living in Australia com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 45 publications
(81 reference statements)
3
33
0
1
Order By: Relevance
“…Refugees are at elevated risk of poor physical and mental health during the COVID-19 pandemic (Júnior et al, 2020 ), in part due to prior exposure to war and persecution trauma (Liddell et al, 2021 ) and significant daily stressors in the post-displacement or migration environment. Despite the effectiveness of vaccines to reduce the contagion and severity of SARS-CoV-2 infections (Khoury et al, 2021 ), many people including refugees and migrants (Australian Red Cross, 2021 ) are hesitant to be vaccinated (Robinson, Jones, Lesser, & Daly, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Refugees are at elevated risk of poor physical and mental health during the COVID-19 pandemic (Júnior et al, 2020 ), in part due to prior exposure to war and persecution trauma (Liddell et al, 2021 ) and significant daily stressors in the post-displacement or migration environment. Despite the effectiveness of vaccines to reduce the contagion and severity of SARS-CoV-2 infections (Khoury et al, 2021 ), many people including refugees and migrants (Australian Red Cross, 2021 ) are hesitant to be vaccinated (Robinson, Jones, Lesser, & Daly, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…asylum seekers' previous experiences with authorities in their home countries, it is not unreasonable to expect lower trust in authorities in this group (cf. [ 35 ]. A Norwegian study found that most migrants reported a high level of adherence to preventive measures (88%) and trust in Norwegian authorities (79%) [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among 56 refugee and asylum seekers in Australia, COVID-19 infection stressors (e.g., worry about being infected) was related to health anxiety symptoms at a cross-sectional level ( Liddell et al, 2021 ). Newby, O'Moore, Tang, Christensen, and Faasse (2020) examined cross-sectional relations between COVID-19 worry and mental health among a large sample of adults from Australia ( n = 5071) and found worry about contracting COVID-19 was a significant predictor of depression and anxiety whereas worry about a loved one contracting COVID-19 was associated with anxiety and stress.…”
Section: Narrative Reviewmentioning
confidence: 99%